Geological Composition and Structure of the Filling Zone and Its Water-Resisting Property Evaluation on the Top of Ordovician Limestone - Qiqing Wang; Wenping Li; Qiangqiang Liu (Geofluids)
With the gradual increase in mining depth of coal fields in North China, the threat posed by karstic Ordovician limestone water to the safe stoping of mines is becoming increasingly prominent. Investigating the water-resisting property of the filling zone on the top of the Ordovician limestone provides the key to safe mining under pressure. This paper analyzed the formation process of the filling zone on the top of Ordovician limestone in North China, and by combining analysis results of several geological field investigations on Ordovician outcrops, the filling zone on the top of Ordovician limestone was divided into three water-resisting structures: (1) completely filled, (2) incompletely filled, and (3) nonfilled. Based on the lithological composition, logging curves, and the water inflow status of several field boreholes, various characteristics of these clay-filled zones were used to determine the mudstone content from top to bottom. Using the interbedded mudstone thickness ratio, relative argillaceous content, impermeable filling zone thickness, rock quality designation (RQD), and faulting as evaluation factors, this paper evaluated the water-resisting property of the filling zone in the study area based on feature-weighted fuzzy C-means clustering (WFCM) algorithm and determined the extent of each zone. The completely filled zone accounts for 46.9% of the total area, incompletely filled zone accounts for 23.9%, and the zone not filled with clay material accounts for 29.2%. As indicated by field investigations on the boreholes, the actual percent of each zone is similar to the theoretical results. The study results present a vital guide for Ordovician limestone water control in deep mining.